7
$\begingroup$

Suppose If $x^2 +px +1$ is a factor of $ax^3 +bx+c$ then relate $a,b,c$ such that $a,b,c \in R$

I can write $$ax^3 +bx+c=(x^2 +px +1)(\lambda x +D)$$ $$\implies ax^3 +bx+c =\lambda x^3 + x^2.p\lambda + x(\lambda+pD)+D $$ and then compare coefficient to find out relation but that will be long and tedious process , I want shorter approach to this problem . Btw I was given following options for this question

A) $a^2+c^2+ab=0$

B) $a^2-c^2+ab=0$

C) $a^2-c^2-ab=0$

D) $ap^2+bp+c=0$

Maybe we can relate something by looking at options?

| cite | improve this question | | | | |
$\endgroup$
11
$\begingroup$

Just observe that the product of two roots of the quadratic is $1$. So the third root has to be $\frac{-c}{a}$. Now substitute this root instead of $x$ in the cubic.

| cite | improve this answer | | | | |
$\endgroup$
  • $\begingroup$ This is genious , awesome $\endgroup$ – Tesla Mar 25 '15 at 6:17
3
$\begingroup$

You should have $(x^2+px+1)(\lambda x + D) = \lambda x^3 + (p\lambda + D) x^2 + (pD + \lambda) x + D$. thus $D = c$ and $\lambda = a$, and you need $p \lambda + D = ap + c = 0$ and $pD + \lambda = cp + a = b$. Eliminating $p$ from these two gives you $0 = c (ap + c) - a(cp + a - b) = \ldots$.

| cite | improve this answer | | | | |
$\endgroup$
0
$\begingroup$

Following the path you have taken, and correcting the algebra, one Gets

$$(\lambda X+D)(X^2+pX+1)=\lambda X^3+(\lambda p+D)X^2+(Dp+\lambda)X+D$$

And this is valid for all $X$. So by identifying the coefficients we get

$$\begin{cases} \lambda=a\\ \lambda p+D=0\\ Dp+\lambda=b\\ D=c \end{cases}$$

which reads

$$\begin{cases} a p+c=0\\ cp+a=b\end{cases}$$

and this leads to

$$-\frac{c^2}{a}+a=b$$

$$a^2-c^2-ab=0$$

| cite | improve this answer | | | | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.